Doing Planning and Task Performance in Second Language Acquisition: An Ethnomethodological Respecification. Issue 4 (2nd September 2013) - Markee, Numa; Kunitz, Silvia
Abstract : We use insights and methods from ethnomethodological conversation analysis and discursive psychology to develop an account of embodied word and grammar searches as socially distributed planning practices. These practices, which were produced by three intermediate learners of Italian as a Foreign Language (IFL), occurred massively in natural data that were gathered during a 3‐week period from a third‐semester IFL course at a university in the United States. We develop a behavioral analysis of these data that shows: (1) what participants do during planning talk and how they do such talk and (2) whether they actually do what they planned to do.